PENERAPAN “KNOWLEDGE SHARING” DALAM KEGIATAN “OVERNIGHT STAY AT LIBRARY” BERSAMA PEGIAT LITERASI DI SUMATERA BARAT: Studi Kasus Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Fatma , Riska (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2022)
Awareness of the importance of information and knowledge is felt by individuals because of the need that is always driven by information. Knowledge is an important asset to improve abilities and survival skills in dynamic activities. The emergence of various communities or movements such as literacy activists in the library aims as an effort to become a learning community in utilizing information into useful knowledge for people's lives. This article discusses the implementation of "knowledge sharing" in the "Overnight Stay at Library" activity with literacy activists in West Sumatra. This type of research is qualitative using case study method. The case study method is used to see how the implementation of “knowledge sharing” of literacy activists and the role of the Department of Archives and Libraries of West Sumatra Province in supporting and facilitating the community of literacy activists in increasing the literacy index in West Sumatra. The result of this research is that the information transfer process is dominated by activities in the socialization process. This can be seen in the "knowledge sharing" carried out by the Head of the Department, librarians, and participants in the "Overnight Stay at Library" event during the two days and one night event at the Archives and Library Office of West Sumatra Province. With the "knowledge sharing" process, the knowledge that comes from the tacit knowledge of each participant turns out to be widely revealed and conveyed. The role of the library is very influential on the growth of information and knowledge of the people of West Sumatra.